Implant-Based Breast Reconstruction Using a Polyester Mesh (Surgimesh-PET): A Retrospective Single-Center Study. Issue 6 (June 2016) - Baldelli, Ilaria; Cardoni, Gaia; Franchelli, Simonetta; Fregatti, Piero; Friedman, Daniele; Pesce, Marianna; Ponte, Erica; Santori, Gregorio; Santi, Pierluigi
Abstract : Background: Although the introduction of acellular dermal matrices is considered one of the most important advancements in alloplastic breast reconstruction, costs and local policy limit their use in Italy. The purpose of this study was to assess short-term outcomes following Surgimesh-PET–based breast reconstruction. Methods: A single-center, retrospective, case-control study was performed from January 1, 2012, to December 31, 2013, by enrolling 206 breast reconstructions performed in 196 patients after oncologic ( n = 200) or prophylactic ( n = 6) mastectomy. Group A included 63 patients who underwent 70 immediate Surgimesh-PET–assisted breast reconstructions, and group B included 133 patients who underwent 136 standard breast reconstructions. Results: No significant differences between groups occurred for early postoperative complications ( p = 0.610), major complications that required surgical revision ( p = 0.887), volume ( p = 0.498) or width of the prosthesis ( p = 0.201), skin-sparing mastectomy ( p = 0.315), or axillary surgery ( p = 0.265). Multivariate logistic regression showed that prior radiotherapy was the only significant variable for early postoperative complications in both whole series ( p = 0.011) and group B ( p = 0.046), whereas body mass index greater than 25 was an independent predictor in group A ( p = 0.041). Prior radiotherapy was the only variable that reached statistical significance in the multivariate model for major complications in the whole series ( p = 0.005). Conclusions: Short-term outcomes of Surgimesh-PET–based alloplastic breast reconstruction are promising. Further studies are needed to evaluate the long-term results of this surgical approach. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.